(untitled) - 1980-; Harbour, David; 1975-; Kurylenko, Olga; Fagbenle, O-T; 1979-; Hurt, William; Winstone, Ray; 1957-; Weisz, Rachel; 1970-; Pearson, Eric; et al. ([Burbank, California], 2021)
Natasha Romanoff aka Black Widow confronts the darker parts of her ledger when a dangerous conspiracy with ties to her past arises.
Keywords: Black Widow; (Fictitious character); Drama; Spies; Drama; Conspiracies; Drama; Video recordings for people with visual disabilities; Video recordings for the hearing impaired; Action and adventure films; Superhero films; Fiction films; Feature films